Inventarisasi Semut Arboreal (Hymenoptera: Formicidae) di Kawasan Air Terjun Sarasah Uwak - Anggun Rafila . (Jurnal Serambi Biologi, 2023)
Arboreal ants are ants that have dominant activity in trees. Several abiotic and biotic factors in trees affect the species of ants found, such as nesting sites, food sources and insect symbionts. This study aims to inventory arboreal ant species in the Sarawak Uwak waterfall area. The research was conducted on November 27, 2022, using the Beating method for collecting insects. The results found 48 individual arboreal ants, which belong to 10 species and 8 genera. In the Camponotus and Polyrachis genera each found 2 species, while in the genera Myrmicaria, Technomyrmex, Acanthomyrmex, Colobsopsis, Odontomachus and Pheidole each found 1 species.